Supermicrosurgical treatment for lymphedema: a systematic review and network meta-analysis protocol - Will, PA; Wan, Z; Seide, SE; Berner, JE; Kneser, U; Gazyakan, E; Hirche, C (BioMed Central, 2022)
Background Lymphedema is a condition that affects up to 130 million subjects worldwide. Since it is related to several complications and a significant reduction in terms of quality of life, it is a heavy burden not only to the patients but also for the healthcare system worldwide. Despite the development of supermicrosurgery, such as vascularized lymph node transfer (VLNT) and lymphovenous anastomosis LVA, the indications and outcomes of these complex groups of interventions remain a controversial topic in the field of reconstructive plastic surgery. Methods This systematic review and network meta-analysis aims to assess the evidence of outcomes of LVA and VLNT in patients with lymphedema. Secondary aims of the project are to determine if for any outcomes, LVA or VLNT is superior to conservative therapy alone, and whether the available evidence favors any kind of supermicrosurgical interventions for lymphedema patients. This study will include original studies of patients with lymphedema on the extremities indexed in PubMed, EMBASE, CENTRAL, PASCAL, FRANCIS, ISTEX, LILACS, CNKI, and IndMED that reported microsurgery (supermicrosurgery) of all techniques aiming the re-functionalization of the lymphatic system. As comparators, mere observation, conservative treatment of any kind, and the other subgroups of supermicrosurgery are planned. The primary outcome of this systematic review and network meta-analysis is the difference of the limb volume, while the secondary outcomes of interest will be erysipelas rates, major and minor complications, postoperative necessity of continuous compression garments, and patient satisfaction, measured by already published and validated scores for quality of life. Discussion We will provide an overview and evidence grade analysis of the scientific literature available on the effectiveness of the subcategories of supermicrosurgical interventions for lymphedema.